2019
DOI: 10.15835/nbha47311490
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Photosynthetic Pigments, Phenolic, Glucosinolates Content and Antioxidant Capacity of Broccoli Sprouts in Response to Nanoselenium Particles Supply

Abstract: Improving the nutritional quality of plants has emerged from the fact that macro- and micro- nutrients are limited in various agricultural areas. The aim of our study was the biofortification of broccoli sprouts with selenium nanoparticles (NSePs) and evaluation of growth parameters, assimilator pigments content, total phenols, glucosinolates content along with antioxidant capacity, in order to boost value added output, such as improved nutrition and food functionality. NSePs were prepared by reduction of NaHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Nonetheless, the number of studies, which determined the nutritional composition of broccoli seedlings and the variations occurring during germination, is significantly smaller than that of glucosinolates and phenolic compounds. These studies indicated that broccoli sprouts are expressly rich in vitamins (A, C, K, and folic acid), minerals (potassium, calcium, magnesium, and selenium), pigments (carotenoids and chlorophylls) and some other important nutrients (amino acids, fatty acids, and dietary fiber) [20][21][22]51,57,85,86]. In general, the biochemical composition of broccoli sprouts and microgreens depends mainly on the germination time, and 8-day-old sprouts displayed the highest nutrient concentration [22].…”
Section: Other Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the number of studies, which determined the nutritional composition of broccoli seedlings and the variations occurring during germination, is significantly smaller than that of glucosinolates and phenolic compounds. These studies indicated that broccoli sprouts are expressly rich in vitamins (A, C, K, and folic acid), minerals (potassium, calcium, magnesium, and selenium), pigments (carotenoids and chlorophylls) and some other important nutrients (amino acids, fatty acids, and dietary fiber) [20][21][22]51,57,85,86]. In general, the biochemical composition of broccoli sprouts and microgreens depends mainly on the germination time, and 8-day-old sprouts displayed the highest nutrient concentration [22].…”
Section: Other Compoundsmentioning
confidence: 99%
“…Among these compounds, carotenoids and chlorophylls were determined in several studies of broccoli sprouts [20,50,51,73,79]. Carotenoids are a group of isoprenoid molecules synthesized as secondary metabolites by all photosynthetic plants, including broccoli [87].…”
Section: Other Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials (1-100 nm) represent another intriguing subject for sprouting. The effect of nano-silver (NAg) was studied in radish sprouts [97], and that of nano-selenium (NSe) in broccoli sprouts [98]. High levels (600 and 800 ppm) of CO 2 , previously shown to induce plant defenses [99], was applied in the sprouting of pea with positive effects on nutritional traits [100].…”
Section: Delving Into Elicitorsmentioning
confidence: 99%
“…The investigation of different nanoparticles in plant assays has two major purposes. The first one is to find applications of nanotechnology in the agriculture sector (Vicas et al, 2019), as nano-fertilizers, new tools to deliver particular bioactive molecules to manipulate plant breeding and genetic transformation, new approaches for intracellular labeling and imaging, and potential agents with beneficial effects under adverse environmental conditionseg. heavy metal stress.…”
Section: Triticum Aestivum Assaymentioning
confidence: 99%